20.1k views
0 votes
Given f(x) = 3(x2 - 5) + 1 Find f(-3)

User AConsumer
by
5.4k points

2 Answers

2 votes

Answer:

f(-3) = -32 for f(x) = 3(2x - 5) + 1

f(-3) = 13 for f(x) = 3(x^2 - 5) + 1

Explanation:

f(x) = 3 (2x - 5) + 1

f(-3) = 3 (2(-3) - 5) + 1

f(-3) = 3( -6 - 5 ) + 1

f(-3) = 3( -11 ) + 1

f(-3) = -33 + 1

f(-3) = -32

_________

f(x) = 3(x^2 - 5) + 1

f(-3) = 3((-3)^2 - 5) + 1

f(-3) = 3(9 - 5) + 1

f(-3) = 3(4) + 1

f(-3) = 12 + 1

f(-3) = 13

User Joy
by
5.4k points
5 votes

Answer:

f(-3)=3(-3²-5)+1

=3(9-5)+1

=3(4)+1

=12+1

=13

User Schalton
by
6.2k points